Length-weight relationship and condition factor of common ponyfish, Leiognathus equulus (Forsskål, 1775) in Pabean Bay, Indramayu, West Java - Reiza Maulana Aditriawan; Nico Runtuboy (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2017)
This study is aimed to determine length-weight relationship and condition factor of common ponyfish in Pabean Bay, Indramayu. The study was carried out for one year, from April 2016 to March 2017. Fish collection were caught using gillnet and set net. total of 154 individual fishes were caught, the fish samples ranged from 18 - 141 mm in length and 0.05 – 41.35 g in weight. The length-weight relationship of ponyfish throughout a year was W = 7x10-06 L3,1983. The result indicated that the growth pattern of fish was positive allometric. The relative condition factor of ponyfish was varied from 0,67 – 1,42 Abstrak Penelitian ini bertujuan untuk menentukan hubungan panjang bobot dan faktor kondisi ikan petek yang ada di Teluk Pabean, Indramayu. Penelitian dilaksanakan selama satu tahun dari bulan April 2016 hingga bulan Maret 2017. Ikan contoh ditangkap dengan menggunakan alat tangkap yaitu jaring insang dan sero. Jumlah ikan yang tertangkap seba-nyak 154 ekor dengan kisaran panjang total 18 - 141 mm dan bobot 0,05 – 41,35 g. Hubungan panjang-bobot ikan petek sepanjang tahun 2016 adalah W = 7x10-06 L3,1983. Hasil ini menunjukkan bahwa pola pertumbuhan ikan bersifat alome-trik positif. Faktor kondisi ikan petek berfluktuasi berkisar antara 0,67 – 1,42.